Status of heavy metals concentrations in oysters (Crassostrea sp.) from Setiu wetlands, Terengganu, Malaysia = Status kepekatan logam berat dalam tiram (Crassostrea sp.) dari tanah bencah Setiu, Terengganu, Malaysia - Shaari, Hasrizal; Raven, Bryan; Sultan, Khawar; Mohammad, Yuzwan; Yunus, Kamaruzzaman (Penerbit UKM, 2016)
This study aimed at documenting the potentially toxic metal levels in oysters from the aquaculture area of the Peninsular Malaysia east coast. Concentrations of essential (Zn and Cu) and non-essential (Pb and Cd) heavy metals were analyzed in total soft tissue, different sex, selected organs and shells of Crassostrea sp. from cultured and wild area of Setiu Wetlands. The heavy metal contents among the sampling sites are statistically not significant (p>0.05) indicating no systematic and site-specific trend between cultured and wild environment. Zinc was the highest metal detected in total soft tissue, sex and shells with the mean concentration of 28.55±6.76, 30.55±3.89 and 8.22±2.98 μg/g, respectively. The analysed metals were highly accumulated in gills than other organs with the mean value of 74.11±13.03 μg/g of Zn, 4.82±0.82 μg/g of Cu, 0.61±0.06 μg/g of Pb and 0.45±0.1 μg/g of Cd. The varying metals content in the different soft tissues might be due to the different affinity of metals that bind with metallothioneins. The metal levels measured in oysters did not exceed the maximum permissible limits for Zn, Cu, Pb and Cd. The measured metal levels may represent baseline values reflecting background conditions that contain a certain degree of human impact.